(untitled) (Biological Sciences - PJSIR, 2006)
The geochemical properties of roadside soils, specifically the association of metals with operationally defined solid fractions, were characterised. The new optimised four-step (acid extractable, reducible, oxidizable, and residual) sequential extraction procedure was applied to five roadside soils from an urban city, Lagos, Nigeria. Three elements were examined (Pb, Cu and Zn) in the < 250-?m fraction. Data so obtained indicated that more than 50% of the metals were associated with the residual fraction, reflecting lithogenic-pedogenic control. Zinc had one-sixth of its quantity in the most mobile and/or bioavailable fraction, which is susceptible to release into solution with the decrease in pH. The amount of lead associated with the reducible fraction was significant, while an appreciable amount of copper was associated with oxidizable fraction (19%).